ALLUSION AS A LINGUISTIC FEATURE OF MODERN ENGLISH LYRICS(ON THE EXAMPLE OF PINK AND MAROON 5) - Sadvakassova, S.B. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
Modern English-language lyrics provide unique opportunities for expanding socio cultural knowledge. Without the necessary minimum knowledge of the language, the history of English-speaking countries, literature, the realities of modern mass culture, it is impossible to speak of full language proficiency. Each lyrics reflects any stories (love, life) of a reference to any event. Recently, a trend has been gaining more and more where singers turn to politics and sing about the global problems of mankind, or write songs with a reference to the country's historical events. The songs have a deep sense of the text, many songs about life situations, calling for friendship, kindness, love. [1-5]
Keywords: stylistics; stylistic means; allusions; social allusions; political allusions; religious allusions; the English language; the texts of modern English language songs